2009
DOI: 10.1016/j.joca.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading highly increases IL-6 production and decreases OPG expression by osteoblasts

Abstract: This work demonstrates that IL-6 is mechano-sensitive cytokine and probably a key factor in the biomechanical control of bone remodeling in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
108
2
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 47 publications
10
108
2
4
Order By: Relevance
“…In fact, previous gene expression studies of cells subjected to large mechanical loads have reported regulation of stress and inflammatory genes. 15,35,36 In comparison, there were no signs of upregulation of inflammatory or stressrelated genes in the present study, supporting the suggestion of an appropriate level of strain being utilized. Our study also showed a markedly lower total number of changes in gene expression in response to a mechanical loading.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In fact, previous gene expression studies of cells subjected to large mechanical loads have reported regulation of stress and inflammatory genes. 15,35,36 In comparison, there were no signs of upregulation of inflammatory or stressrelated genes in the present study, supporting the suggestion of an appropriate level of strain being utilized. Our study also showed a markedly lower total number of changes in gene expression in response to a mechanical loading.…”
Section: Discussionsupporting
confidence: 83%
“…Commonly a gel based scaffold or tissue culture plastic has been used as the substrate on which cells were mechanically loaded, and the strain employed has been in the range of 2%-20%. 6,[12][13][14][15][16][17][18][19][20] Neither the scaffold nor the strain of this magnitude represents the true environment or magnitude of physiological or pathological loading of bone in humans in vivo. Further, a number of studies in vivo have been carried out in an attempt to overcome these obstacles, but these are limited to animal models and therefore could be associated with differences in responses to loading and mechanisms involved from one species to another.…”
mentioning
confidence: 99%
“…In mechanobiological studies, different culture systems and mechanical forces are used for cellular stimulation. Compressive forces, tensile strain, hydrostatic pressure, and shear forces are frequently used as biomechanical stimuli [21][22][23][24]. A well-established device for application of tensile strain was used in our study [17].…”
Section: Discussionmentioning
confidence: 99%
“…2 Although it is impossible to detect the change in bone remodeling on plain radiography alone, magnetic resonance imaging (MRI) and bone scintigraphy have been adopted for this purpose. 3 In our department, we adopted positron emission tomography (PET) for the evaluation of patients with early or pre-osteoarthritis of the hip, and our previous study suggested the usefulness of 18 F-fluoride PET for the early detection of hip osteoarthritis. 4 One question is: what causes bone remodeling acceleration in early stage osteoarthritis?…”
mentioning
confidence: 99%
“…Our hypothesis is that mechanical stress concentration in the hip joint may be related to bone remodeling abnormalities. The purpose of this study was therefore to examine the relationship between mechanical stress distribution calculated by finite element analysis (FEA) and 18 F-fluoride PET uptake in the hip joint.…”
mentioning
confidence: 99%